1987
DOI: 10.2527/jas1987.642414x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Immune Response to Pseudorabies and Atrophic Rhinitis Vaccines: II: Comparison of Additive Direct and Maternal Genetic Effects

Abstract: Data from 52 litters farrowed in two seasons of a cross-fostering experiment were analyzed to estimate variances and covariances for additive direct and maternal genetic effects on immune response to pseudorabies virus and B. bronchiseptica vaccine. Twenty purebred boars and 44 sows of the Duroc, Landrace and Yorkshire breeds were used. Immune response was measured after vaccine challenge. A modified-live pseudorabies (PR) vaccine was administered to piglets at 28 d of age; response was measured by log, serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
9
0
2
Order By: Relevance
“…Heritability was estimated at 0.18. Similar antibody heritabilities were estimated for pure‐bred pigs immunized with two different vaccines 22 . Here low heritabilities of 0.18 ± 0.09 and 0.15 ± 0.07 were recorded for immune response to a modified‐live pseudorabies vaccine and an inactivated bacterial bacterin, respectively, both measured 56 days after inoculation (however, it was 0.52 ± 0.15 for the bacterin after 119 days).…”
Section: Heritable Variation and Contraception Resistancesupporting
confidence: 69%
“…Heritability was estimated at 0.18. Similar antibody heritabilities were estimated for pure‐bred pigs immunized with two different vaccines 22 . Here low heritabilities of 0.18 ± 0.09 and 0.15 ± 0.07 were recorded for immune response to a modified‐live pseudorabies vaccine and an inactivated bacterial bacterin, respectively, both measured 56 days after inoculation (however, it was 0.52 ± 0.15 for the bacterin after 119 days).…”
Section: Heritable Variation and Contraception Resistancesupporting
confidence: 69%
“…The breed rankings differed in Rothschild et al (1984a) and Rothschild et al (1984b) using different antigens. Meeker et al (1987b) estimated the heritability of response to pseudorabies vaccine to be .18 measured at 56 d of age, and the heritabilities of response to B. bronchiseptica vaccine to be .15 and .52 measured at 56 and 119 d of age, respectively. Meeker et al (1987a) showed no evidence for nonadditive genetic control (heterosis) of immune response to pseudorabies or B. bronchiseptica vaccines, but did observe additive genetic control and breed differences similar to Rothschild et al (1984a).…”
Section: Disease Resistance and Immune Responsementioning
confidence: 99%
“…Huang (1977) and Takahashi et al (1984) indicate that larger than trace amounts of specific maternal antibody interfere with active immunity. Immune colostrum interference with active antibody production in pigs for about the first 3 wk reduces the importance of the genetics of a pig in the early stage of immunity development (Hoerlein, 1957;Segre and Kaeberle, 1962a,b;Perry and Watson, 1967;Rothschild et al, 1984a,b;Meeker et al, 1987b).…”
Section: Genetic Control Of Immune Response--the Major Histocompatibimentioning
confidence: 99%
“…Such an effect has been found in previous generations of our lines (Leitner et ah, 1994). Meeker et al (1987) found a maternal effect on the immune response of young pigs. The maternal effect may have either a random or genetic nature, or both.…”
Section: Discussionmentioning
confidence: 95%